2008
DOI: 10.1063/1.3005380
|View full text |Cite
|
Sign up to set email alerts
|

Gyrokinetic turbulence simulations at high plasma beta

Abstract: Electromagnetic gyrokinetic turbulence simulations employing Cyclone Base Case parameters are presented for β values up to and beyond the kinetic ballooning threshold. The β scaling of the turbulent transport is found to be linked to a complex interplay of linear and nonlinear effects.Linear investigation of the kinetic ballooning mode is performed in detail, while nonlinearly, it is found to dominate the turbulence only in a fairly narrow range of β values just below the respective ideal limit. The magnetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
224
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(244 citation statements)
references
References 33 publications
17
224
3
Order By: Relevance
“…On the other hand, the heat flux at β i = 0.6% is one-half of that at β i = 0.2%. One of the reasons is the beta dependence of zonal flow production (Pueschel et al 2008). The zonal flow shearing decreases with beta slower than the linear growth rate.…”
Section: Microturbulence At Finite Beta (Nonlinear Simulations)mentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, the heat flux at β i = 0.6% is one-half of that at β i = 0.2%. One of the reasons is the beta dependence of zonal flow production (Pueschel et al 2008). The zonal flow shearing decreases with beta slower than the linear growth rate.…”
Section: Microturbulence At Finite Beta (Nonlinear Simulations)mentioning
confidence: 99%
“…10(b). It is reported that the transport due to the magnetic flutter is proportional to the square of beta β 2 in ITG turbulence (Pueschel et al 2008), and that is explained by the production of a stochastic magnetic field. The violation of magnetic surface is caused by the production of the tearing parity, as explained in Sec.…”
Section: Impact Of Magnetic Perturbation On Turbulent Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Damped buffer regions of width Δ b =8 ρ s and damping rate ν b =1 c s /a are used at both radial boundaries to prevent profile relaxation [53] and the time-and flux-surface-averaged gradient contribution from the n=0 zonal moments is less than 1% of the equilibrium values. A unique feature of these simulations is that nearly all of the electron thermal transport (~98%) comes from the magnetic flutter contribution (~v ||,e ⋅δB r /B) in contrast to ITG/TEM turbulence, ETG turbulence, or even simulations that approach the ideal or kinetic ballooning mode limit (χ e,em /χ e,tot~5 0%) [55][56][57][58]. In addition there is negligible particle, ion thermal or momentum transport, consistent with strong magnetic flutter contribution and the fact that ions are much heavier than electrons (v ||,i <<v ||,e ).…”
Section: Numerical Gridsmentioning
confidence: 99%